Psychological Wellbeing in Cervical and Breast Cancer Survivors: Differences in Each Stage of Survivorship - Ni Putu Wulan Purnama Sari (Journal of Educational, Health and Community Psychology, 2020)
Being diagnosed with cancer in some females results in impaired psychological wellbeing (PWB). This study aimed to compare and analyze the PWB between cervical and breast cancer survivors (CCS and BCS) especially in each stage of survivorship. This cross-sectional study involved 47 CCS and 58 BCS (n=105) from three districts in Surabaya, Indonesia. QOL-CS was used for collecting data. Independent sample T test, one way ANOVA test, and linear regression test were used in data analysis (Î±<0.05).Â  Results showed that most respondents had sufficient PWB. PWB between cases and survivorship stages was not significantly different (p=0.067 overall, p=0.425 in CCS, and p=0.135 in BCS). In CCS, appearances and self-concept were significantly changing over time (p=0.032 and p=0.007 respectively); meanwhile in BCS, life acceptance, happiness, memory/concentration, and usefulness were continuously changed (p=0.044, p=0.019, p=0.020, and p=0.018 respectively). Appearances were the best predictor of PWB in both cases (p=0.000), but it gave more influences in BCS than CCS (52.6% vs. 29.7%).Keywords: breast cancer, cancer, cancer survivorship, cervical cancer, psychological wellbeing